In vitro antioxidant effects of different extracts obtained from the leaves and seeds of Allium ampeloprasum subsp. persicum - Saba Feghhi-Najafabadi; Leila Safaeian; Behzad Zolfaghari (Shahrekord University of Medical Sciences, 2019)
Introduction: This study evaluated antioxidant effects of hexane, chloroform, chloroform-methanol, aqueous and butanol extracts of leaves and seeds of Allium ampeloprasum subsp. persicum.Methods: Various extracts were evaluated for total phenolic content, ferric reducing antioxidant power (FRAP), 1,1-diphenyl-2-picrylhydrazyl (DPPH) and H2O2 scavenging activities.Results: Total phenolic content varied from 2.46 to 8.12 mg gallic acid equivalents (GAE) per gram for various extracts with the highest level for butanol leave extract. Butanol leave extract showed the lowest IC50 of DPPH scavenging. FRAP assay showed stronger antioxidant capacity for leaves than seeds' extracts and butanol extract was comparable to ascorbic acid at the concentration 50 μg/mL. In H2O2 scavenging activity assay, butanol and chloroform-methanol leave extracts showed the least IC50 value.Conclusion: Our results revealed moderately low amount of phenolic compounds and weak DPPH scavenging activity for all extracts of A. ampeloprasum subsp. persicum. However, leaves extracts showed good total antioxidant capacity and H2O2 scavenging activity.